Ethnobotanical exploration and vegetation analysis of medicinal plants in Makmur Village, Central Tapanuli Regency, Indonesia - Anang Analdi Mario Saruksuk; Yunus Afifuddin (Global Forest Journal., 2026)
Medicinal plants are a biological resource utilised by local communities as a source of traditional treatment. This research was conducted from January to March 2026 in the forest and land areas of Makmur Village, Pasaribu Tobing Subdistrict, Central Tapanuli Regency, to identify local community knowledge, the medicinal plant species used, and the diversity of those species. The research employed a descriptive method combining interviews with a vegetation analysis. The results show that the community continues to use medicinal plants in a manner passed down through generations. A total of 75 species of medicinal plants are used to treat around 22 health complaints and ailments. The plant part most commonly used is the leaf, accounting for 61.33%; boiling is the dominant processing method (60%), and oral consumption (drinking) is the most common method of use (65.33%). The vegetation analysis showed that the dominant species at the understorey/seedling level was hairy melastome (senduduk bulu, Clidemia hirta) with an Importance Value Index (IVI) of 29.08%; at the sapling level, jengkol (Archidendron pauciflorum) with an IVI of 17.85; at the pole level, mahang (Macaranga spp.) with an IVI of 44.10; and at the tree level, mahang with an IVI of 43.61. The Shannon-Wiener diversity index (H′) was 3.40 at the understorey/seedling level, 3.22 at the sapling level, 3.01 at the pole level, and 2.8 at the tree level, indicating a diversity level classified as moderate to high